1993
DOI: 10.1042/bj2930667
|View full text |Cite
|
Sign up to set email alerts
|

NH4+ metabolism and the intracellular pH in isolated perfused rat liver

Abstract: The effects of NH4+ on the intracellular pH (pHi) and on the ATP content in isolated perfused rat liver were studied by 31P n.m.r. spectroscopy. In the initial phase of perfusion an average pHi of 7.29 +/- 0.04 was estimated. The presence of low (0.5 mmol/l) and high (10 mmol/l) doses of NH4Cl induced significant intracellular acidification by -0.06 +/- 0.03 and -0.11 +/- 0.03 pH unit respectively. This effect was in contrast with the transient intracellular alkalinization observed in preliminary studies on is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…This process induced acidification in all three forms, which explains their capacity to regulate their internal pH after severe basification of the cytoplasm. This effect has also been reported by Zange et al (1993) when working with isolates from rat liver incubated in the presence of NH 4 Cl.…”
Section: In Verosupporting
confidence: 62%
See 1 more Smart Citation
“…This process induced acidification in all three forms, which explains their capacity to regulate their internal pH after severe basification of the cytoplasm. This effect has also been reported by Zange et al (1993) when working with isolates from rat liver incubated in the presence of NH 4 Cl.…”
Section: In Verosupporting
confidence: 62%
“…Zange et al (1993) and Henderson et al (1987) reported that in media with HCO ) 3 , the addition of NH + 4 and amiloride or DIDS sharply lowered the pH i in eukaryotic cells. Though the test media used in these experiments were NH 4 + free, the production of NH + 4 by T. cruzi was corroborated by Adroher et al (1988Adroher et al ( , 1998.…”
Section: In Veromentioning
confidence: 97%
“…This observation can be explained by the fact that systemic administration of amiloride also affects the Na + /H + exchanger (IC 50 $84 lM [30]), in the liver. Blocking the Na + /H + exchanger in the liver probably impairs the ammonia detoxification, because the rate of urea synthesis in hepatocytes depends on extrusion of H + [31].…”
Section: Secondary Considerationsmentioning
confidence: 99%